The Sorogan Method in Improving the Competence of Reading the Yellow Book in the Pasca-Amtsilati Dormitory in Jepara - Maula, Rohmatul; Nurdin, Ahmad; Sukarman, Sukarman (Lembaga Yasin AlSys, 2025)
Reading the yellow book (kitab kuning) for students in Islamic boarding schools is very important because various religious studies always use the yellow book as a medium to study it in depth. This research reveals the effectiveness of the sorogan method in improving the competence of reading the yellow book among students of the Pasca-Amtsilati dormitory in Jepara, Central Java. The researcher used a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the research showed that the efforts of teachers in improving the competence of students reading the yellow book through the sorogan method proved to be very effective. It can be seen from the improvement in the quality of students' reading, students' understanding of the contents of the reading, and their skills in explaining the contents of the reading. For this reason, the sorogan method in several Islamic boarding schools must continue to be preserved and developed for the quality of religious education for the nation's future generations. However, learning the Yellow Book has many benefits for students, namely a comprehensive understanding of religion, development of critical thinking skills, strengthening practical experience, and self-identity.